GE_GERICHTE P/11678/2023 vom 6. Mai 2024 - GE Cour de justice (2024)
SÉQUESTRE(MESURE PROVISIONNELLE);SUPPRESSION(EN GÉNÉRAL);PARTIE À LA PROCÉDURE;LÉSÉ;TRUST;AYANT DROIT ÉCONOMIQUE;INTÉRÊT JURIDIQUEMENT PROTÉGÉ;CONFISCATION(DROIT PÉNAL);CRÉANCE;GESTION DÉLOYALE | CPP.115; CPP.118; CPP.382; CPP.263; CP.70; CP.71; CP.158